Transcatheter treatment of mitral regurgitation: Current status and future prospects - Yu-Liang Long (Cardiology Plus, 2020)
In recent years, transcatheter treatment of mitral regurgitation (MR) has been extensively explored and has shown promising results. After transcatheter mitral valve repair (TMVr) with MitraClip has become a routine strategy in patients with symptomatic degenerate MR at prohibitive surgical risk, the benefits of TMVr are now being examined in patients with functional MR (FMR). However, the contradictory observations in COAPT and MITRA-FR clinical trials so far have suggested that only patients with severe FMR disproportionate to left ventricular disorder may benefit from this interventional therapy. Nevertheless, more evidence is required to support this hypothesis. In addition, various new devices have been developed, including two original designs from China Mainland, which have displayed excellent performance. Several percutaneous (femoral vein.transseptal) valves used in transcatheter mitral valve replacement have been developed and have also shown good feasibility. Furthermore, hybrid techniques in MR therapies have been emerging, which may reduce residual MR and improve the treatment effects.